Intermedin1-53 Improves Atherosclerosis by Reducing Local Endothelial Damage via AMPK Signaling Pathway in Obese apoE-Deficient Mice - Zhu HX; Ren JL; Cao WJ; Wang R; Chen LL; Gao Q; Zhou YB (Journal of Inflammation Research)
Han-Xu Zhu,1,* Jin-Ling Ren,2,* Wen-Juan Cao,1 Rui Wang,3 Lei-Lei Chen,1,4 Qing Gao,1 Ye-Bo Zhou1 1Department of Physiology, Nanjing Medical University, Nanjing, Jiangsu, People’s Republic of China; 2Department of Pathology and Pathophysiology, Henan University of Chinese Medicine, Zhengzhou, Henan, People’s Republic of China; 3Laboratory of Cardiovascular Bioactive Molecule, Peking University, Beijing, People’s Republic of China; 4Department of Cardiology, the First Affiliated Hospital of Nanjing Medical University, Nanjing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lei-Lei Chen, Email chenlei19762002@163.com Qing Gao, Email gaoqing@njmu.edu.cnBackground: Atherosclerotic cardiovascular diseases (CVD) are commonly found in obesity. Endothelial inflammation accompanied by oxidative stress is a crucial risk factor and a key initiating step for the pathogenesis of atherosclerosis (AS). In the present study, the role and mechanism of intermedin (IMD), a potent active peptide, in endothelial damage in AS in obese apolipoprotein E-deficient (apoE−/−) mice were investigated.Methods and Results: In vivo, IMD1-53 was infused via Alzet mini-osmotic pump in apoE−/− mice with high-fat diet (HFD) for 4 weeks. In vitro, palmitic acid (PA) and oxidized low density lipoprotein (Ox-LDL) were used to stimulate human umbilical vein endothelial cells (HUVECs) for exploring the potential mechanism of IMD1-53 action on endothelial damage. We found that IMD1-53 application remarkably improved plasma lipid profiles, hepatic lipid accumulation and its cholesterol levels, and vascular lipid accumulation and lesion sizes. Moreover, IMD1-53 markedly increased eNOS expression and decreased the levels of vascular inflammatory factors and ROS. In vitro, the combination of PA and Ox-LDL caused more severe inflammatory and oxidative damages and lower expression of eNOS, which were significantly inhibited by IMD1-53. IMD1-53 notably induced AMPK phosphorylation, and the inhibition of AMPK activation markedly reversed the anti-inflammatory and antioxidant effects of IMD1-53 on PA and Ox-LDL-treated HUVECs.Conclusion: IMD1-53 improves AS partially by reducing endothelial inflammatory and oxidative damage via AMPK signaling pathway and decreasing vascular lipid accumulation involving the improvement of lipid profiles in blood and in liver in a state of obesity. Keywords: intermedin, atherosclerosis, endothelium, inflammation, oxidative stress